2021
DOI: 10.1186/s12903-021-01743-5
|View full text |Cite
|
Sign up to set email alerts
|

Origin of MMP-8 and Lactoferrin levels from gingival crevicular fluid, salivary glands and whole saliva

Abstract: Background Pathologically elevated levels of matrix metalloproteinase-8 (MMP-8) and Lactoferrin in oral fluids have been associated with the presence of gingivitis/periodontitis. This study aimed to assess the origin of MMP-8 and Lactoferrin in periodontitis patients and to identify the degree to which conventional clinical parameters correlate with their presence. Methods A total of ten periodontitis and ten healthy patients were included in this … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Lactotransferrin is a globular glycoprotein that is released in response to bacterial infection and is strongly associated with periodontal disease. Because of its antibacterial activity, a decrease in lactotransferrin can promote bacterial growth [26, 27]. Here, lactotransferrin levels exhibited a 1.6‐fold increase in the case group, probably representing a response to the greater bacterial plaque formation in gingivitis.…”
Section: Resultsmentioning
confidence: 97%
“…Lactotransferrin is a globular glycoprotein that is released in response to bacterial infection and is strongly associated with periodontal disease. Because of its antibacterial activity, a decrease in lactotransferrin can promote bacterial growth [26, 27]. Here, lactotransferrin levels exhibited a 1.6‐fold increase in the case group, probably representing a response to the greater bacterial plaque formation in gingivitis.…”
Section: Resultsmentioning
confidence: 97%
“…The collection of gingival fluid is performed using the intracrevicular washing technique (using two injection needles) or the absorption technique using paper strips placed in the gingival crevice [ 91 , 93 ]. It is also important to note that, according to Ramenzoni et al [ 96 ], the highest amounts of MMP-8 come specifically from gingival fluid. According to most studies, patients with periodontitis have higher concentrations and an elevated enzymatic activity of MMP-8 in the gingival fluid compared to healthy individuals [ 93 , 94 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 ].…”
Section: Importance Of Mmp-8 In Periodontitismentioning
confidence: 99%
“…It is also important to note that, according to Ramenzoni et al [ 96 ], the highest amounts of MMP-8 come specifically from gingival fluid. According to most studies, patients with periodontitis have higher concentrations and an elevated enzymatic activity of MMP-8 in the gingival fluid compared to healthy individuals [ 93 , 94 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 ].…”
Section: Importance Of Mmp-8 In Periodontitismentioning
confidence: 99%
See 1 more Smart Citation
“…In the oral cavity, it was found that gingival crevicular fluid levels of calprotectin have positive correlation with worsened clinical findings and elevated inflammatory biomarkers of periodontitis, which is a highly prevalent chronic inflammatory oral disease [ 3 , 12 ]. High salivary lactoferrin concentrations were also found to be well-correlated with increased probing depth in periodontitis patients [ 10 , 13 ].…”
Section: Introductionmentioning
confidence: 99%